Estradiol-dependent axogenesis and Ngn3 expression are determined by XY sex chromosome complement in hypothalamic neurons - Cisternas, Carla Daniela (2020)
Hypothalamic neurons show sex differences in neuritogenesis, female neurons have longer axons and higher levels of the neuritogenic factor neurogenin 3 (Ngn3) than male neurons in vitro. Moreover, the effect of 17-β-estradiol (E2) on axonal growth and Ngn3 expression is only found in male-derived neurons. To investigate whether sex chromosomes regulate these early sex differences in neuritogenesis by regulating the E2 effect on Ngn3, we evaluated the growth and differentiation of hypothalamic neurons derived from the “four core genotypes” mouse model, in which the factors of “gonadal sex” and “sex chromosome complement” are dissociated. We showed that sex differences in neurite outgrowth are determined by sex chromosome complement (XX > XY). Moreover, E2 increased the mRNA expression of Ngn3 and axonal length only in XY neurons. ERα/β expressions are regulated by sex chromosome complement; however, E2-effect on Ngn3 expression in XY neurons was only fully reproduced by PPT, a specific ligand of ERα, and prevented by MPP, a specific antagonist of ERα. Together our data indicate that sex chromosomes regulate early development of hypothalamic neurons by orchestrating not only sex differences in neuritogenesis, but also regulating the effect of E2 on Ngn3 expression through activation of ERα in hypothalamic neurons.